2009
DOI: 10.4103/0971-6203.56085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiation doses using weight-based protocol and dose modulation techniques for patients undergoing biphasic abdominal computed tomography examinations

Abstract: Computed tomography (CT) of the abdomen contributes a substantial amount of man-made radiation dose to patients and use of this modality is on the increase. This study intends to compare radiation dose and image quality using dose modulation techniques and weight- based protocol exposure parameters for biphasic abdominal CT. Using a six-slice CT scanner, a prospective study of 426 patients who underwent abdominal CT examinations was performed. Constant tube potentials of 90 kV and 120 kV were used for all arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Philips also advised against using ZDOM due to concerns that use of this system may result in the tube current being inappropriately low in smaller and less attenuating regions such as the head. As ACS was not utilized, weight-based CT protocols were developed using the methodology described by Livingstone et al [22]. On the basis of initial clinical experience with the system, DDOM was deactivated for all patients scanned with their arms down, as the downward modulation of tube current in the AP and posteroanterior (PA) projections was considered inappropriately large because of the presence of the arms resulting in a very high lateral : AP attenuation ratio (Philips protocol 1).…”
Section: Scan Protocolsmentioning
confidence: 99%
“…Philips also advised against using ZDOM due to concerns that use of this system may result in the tube current being inappropriately low in smaller and less attenuating regions such as the head. As ACS was not utilized, weight-based CT protocols were developed using the methodology described by Livingstone et al [22]. On the basis of initial clinical experience with the system, DDOM was deactivated for all patients scanned with their arms down, as the downward modulation of tube current in the AP and posteroanterior (PA) projections was considered inappropriately large because of the presence of the arms resulting in a very high lateral : AP attenuation ratio (Philips protocol 1).…”
Section: Scan Protocolsmentioning
confidence: 99%
“…These results were parallel to the results obtained from our study. In another study carried out by S. Livingstone et al (7) on contrast-enhanced biphasic abdominal examinations, dose reductions between 16% and 28% were achieved with the protocol using ATCM compared to fixed current protocols based on patient weight. According to the results of our study, dose reduction rates were observed approximately between 10% (group 3) and 35% (group 1) among the 3 groups when both phases were considered together (Table 5).…”
Section: Discussionmentioning
confidence: 93%
“…In the literature, studies carried on the abdominal CT examinations of adults report commonly that the use of AEC techniques leads to a considerable decrease in patient dose while keeping a reasonable image quality (6,7,8,9,10,11,12,13,14). This study aims to focus on the use of Z-DOM in contrast-enhanced biphasic abdominal examinations and to make evaluations on image quality and patient dose.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these desirable gains, the low-kilovoltage technique is not frequently applied at most CT departments due to lack of familiarity with appropriate kilovoltage and milliamperage selections and other parameter adjustments that negatively affect the CT workflow (19). The kilovoltage selections can be based on body size (body mass index, abdominal girth, or total weight) and require end-user adjustments in other scanning parameters ( Table 2) (19)(20)(21).…”
Section: Dect Scannersmentioning
confidence: 98%